Political Analysis of Decentralization : Capturing the Stakeholder Perspective Lessons from the Bangladesh Study - Rudra, Nita (World Bank, Washington, DC, 2012)
The objective of this note is to provide guidance to the World Bank task teams engaged in supporting decentralization reform on useful approaches to understanding the broader political dynamics which may affect their operations and dialogue. It does this by synthesizing lessons from an analysis of the political economy of decentralization in Bangladesh, which was carried out to support the World Bank operational engagement.